FEATURES OF CREATING AN INTERNET STORE TO ATTRACT NEW BUYERS IN MODERN CONDITIONS - PUKHALSKA, Yana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In the article the current root principle of creation template Internet shop from domestic representative of small business. Considered preference creation and operation of an online store for buyers and sellers, compared the cost and timing of development and works to create an online store domestic services. The possibility of persons without specific knowledge in the field of site building independently create their own Internet shop for a short time and with minimal costs. Advertising on the Internet allows you to promote the product even at the lowest possible budget, but it is better to use the most effective options. The level of income depends directly on how well the idea will work, so it is recommended to promote the product in any possible way. The main purpose of creating an online store is to increase the volume of enterprise activity, expand sales markets (expand geography), improve the company's image in the market, increase the strength of the enterprise.The purpose of the article is to determine the feasibility of creating an online store in modern conditions of development and calculation of key indicators that will help the entrepreneur to determine the benefits of opening an online store to sell their products in domestic and foreign markets.
Keywords: е-commerce; SEO; website; Internet-shop; promotion Internet-shop; site for business